Promoting The Usage of Business Model Canvas for Tourism Development in Sugihmukti Village, Bandung Regency - Aisha Nur Izzati; Irni Yunita; Fajar Sidiq Adi Prabowo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Based on Decree No. 556/Kep.770-Disbudpar/2022, issued in 2002, Sugihmukti Village in Bandung Regency was officially designated as a tourism village. Sugihmukti Village is known for its birdwatching activities conducted in collaboration with "Burung Indonesia" community which have drawn both domestic and international visitors. Aside from birdwatching, the tourist attractions offered by Sugihmukti Village are not significantly different from those of nearby villages. As a result, Sugihmukti Village is striving to enhance its brand recognition among tourists. We believe that through business model design training, the residents of Sugihmukti Village can uncover their hidden potential and establish a sustainable economic foundation for the future. Economic development at the village level plays a crucial role in improving community welfare. To promote economic development, training about designing business model in Sugihmukti Village is required. This training aims to empower the local community with skills that can boost the village's competitiveness and eventually economic welfare. Thus, a training session titled “Business Model Design Training in Sugihmukti Village, Bandung Regency.” This training is expected to have a significant positive impact on Sugihmukti Village by raising awareness on value proposition, optimizing local resources to enhance key activities, developing partnerships and networks, ensuring sustainability and risk mitigation, and improving community welfare. The delivery method of this training is a direct approach to the residents of Sugihmukti Village particularly those who are directly involved in managing the tourism village. The training is designed to deliver an effective learning process that will enhance both individual and group competencies in tourism. Hopefully, through this training, Sugihmukti Village can present itself as a unique and attractive tourist destination.